PERSEPSI BELANJA MENGGUNAKAN APLIKASI E-WALLET - Riza Hardianti Utari; Tri Kartika Pertiwi (Journal of Information System, Applied, Management, Accounting and Research, 2021)
Digital payment services (fintech payment) are increasingly popular along with the increasing use of smartphones, one of which is electronic payment via e-wallet or digital wallet which is considered to have benefits, ease, and benefit with the many promos on offer. The purpose of this study was to determine and analyze consumer behavior in making purchasing decisions using the E-Wallet DANA application in Indonesia.The sample in this study were users of DANA applications in Indonesia aged over 17 years and transactions not more than the last two months using the DANA application. This study used a purposive sampling technique with the size of the sample used was 120 respondents.The data analysis technique in this study used the Structural Equation Model - Partial Least Square (SEM-PLS). The results of the study concluded that: (1) Perceptions of Awareness through Consumer Attitudes significantly influence Purchasing Decisions, (2) Perception of Ease of Use through Consumer Attitudes significantly influence Purchasing Decisions, (3) Sales Promotion through Consumer Attitudes significantly influence Purchasing Decisions, (4 ) Pleasure Perception has a significant influence on Purchasing Decisions, (5) Perceived Ease of Use has a significant influence on Purchasing Decisions, (6) Sales Promotion has a significant influence on Purchasing Decisions, (7) Consumer Attitude has a significant influence on Purchasing Decisions.